Dental and Oral Hygiene Counseling in Support of National Resilience in the Health Sector in Kabupaten Blitar-Indonesia: PENYULUHAN HIGIENITAS GIGI DAN MULUT DALAM RANGKAMENDUKUNG KETAHANAN NASIONAL BIDANG KESEHATAN DIKABUPATEN BLITAR - Alfiatuz Zahro Al Istiqlaliyah; Krisno Wicaksono, Yudi (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2024)
In an effort to overcome oral health problems that are often faced by the people of Kabupaten Blitar-Indonesia, counseling on oral hygiene was conducted. This activity aims to not only alleviate local health problems but also support the strengthening of national resilience in the health sector. This research uses the ABCD (Asset-Based Community Development) method, which focuses on community empowerment through identifying and utilizing their assets. Through the concepts of national resilience and oral hygiene, this research aims to provide practical solutions for preventing and addressing oral health problems for both citizens and national interests. The education and counseling carried out are expected to increase community knowledge and understanding of the importance of maintaining oral hygiene as part of disease prevention efforts. The results achieved from this study include increased community participation in health programs, especially in the field of oral health. These results indicate an increased collective understanding of the importance of oral hygiene and how it has the potential to have a long-term positive impact on public health. This research reaffirms that improving the quality of oral health is a fundamental step in strengthening national resilience in health. Through it, the community becomes more self-reliant.